Residue Analysis and Dietary Risk Assessment of 10 Neonicotinoid Insecticides in Oenanthe javanica from Hainan Province of China - Shusheng Tang; Zikang Zeng; Rui Kang; Ying Wei; Gaohao Tan; Minni Chen; Bin Wang; Zhuhua Tang (Foods)
In this study, residues of 10 neonicotinoid insecticides were tested with 143 fresh samples of Oenanthe javanica using the QuEChERS method combined with UPLC-MS/MS. Based on the residue results, the point estimation method was used to assess dietary risks for adults and children, and the cumulative risk was assessed according to the hazard index (HI) and relative potency factor (RPF) methods. The results showed that 71 out of 143 samples of fresh Oenanthe javanica sold in Hainan tested positive for neonicotinoid insecticides, with a detection rate of 49.65%. Six neonicotinoid insecticides were detected and their detection frequencies are as follows: imidacloprid (44.76%), acetamiprid (16.08%), clothianidin (13.29%), dinotefuran (4.90%), thiamethoxam (3.50%) and flonicamid (3.50%). The most frequently co-detected combination was imidacloprid and acetamiprid, with a detection rate of 29.58%. The results of acute and chronic dietary risks showed that all the obtained values of %ADI (acceptable daily intake) and %ARfD (acute reference dose) are far below 100%, so the risks of the six detected neonicotinoid insecticides are acceptable for various population groups. Meanwhile, the results of the cumulative risk showed that all the obtained values of the hazard index and the corrected total exposure concentration are far lower than the health guidelines, indicating that the residue levels of neonicotinoid insecticides in fresh Oenanthe javanica are acceptable. However, it is notable that its acute risk is higher than its chronic risk, and the dietary risk for children is higher than adults. These findings will provide a theoretical basis and objective data for supporting the revision of MRLs for Oenanthe javanica, as well as valuable guidance for the production, consumption, regulation and standardization of Oenanthe javanica sold in Hainan.